Four cases of pulmonary thromboembolism diagnosed by endobronchial ultrasound. Issue 7 (3rd November 2016) - Erer, Onur Fevzi; Cimen, Pinar; Unlu, Mehmet; Katgi, Nuran
ABSTRACT: Endobronchial ultrasound (EBUS) is a technique for the detection of mediastinal abnormalities. A total of 548 EBUS procedures were performed for various indications, and in four cases (0.7%), filling defects in central pulmonary arteries were demonstrated fortuitously during the procedure. Subsequently, all patients underwent contrast‐enhanced CT of the thorax to confirm the diagnosis of pulmonary thromboembolism (PTE). In three of the four cases, there was a concomitant lung cancer. PTE can be incidentally detected during EBUS; therefore, pulmonary arteries should be examined carefully during EBUS in all patients, particularly in patients with suspected or proven malignancy. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 45 :441–444, 2017